A sign of affection. 12 - Dashiell, Christine, 1984-; Vanstiphout, Carl; Blakeslee, Lys, 1985- (Kodansha Comics, an imprint of Kodansha USA Publishing, LLC, 2025)
"Yuki is a typical college student--it's just that she can't hear. A chance encounter on a train leads to a serious crush...but will he give her a chance? A sweet and relatable manga romance from the creator of Shortcake Cake! 'Today, I hope we have fun to the very end.' Yuki and Itsuomi have grown even closer since Itsuomi opened up about his past. When Oushi invites the two of them to an amusement park for the day, Itsuomi is determined to have a good time, while Yuki is apprehensive about whether the boys will get along. As Oushi's supportive friends keep an eye on the trio from the bushes, will Oushi finally be able to tell Yuki what he's always wanted to say to her... ." --